ESTIMATION OF THE EFFECT OF PARTINGS TO THE QUALITY OF RECOVERABLE LIGNITE MINED FROM MULTI-LAYERS DEPOSITS - Γαλετάκης, Μ.; Παπανικολάου, Κ. (Bulletin of the Geological Society of Greece, 2004)
The evaluation of multi-layers lignite deposits is mainly based on borehole data. The lack of sufficient number of analytical data of waste and carbonaceous layers, leads to the use of indicative values during the evaluation and consequently affects the estimation precision of recoverable lignite quality. In the present work the possibility of determination of basic quality parameters of waste and carbonaceous layers by using an expert system was investigated. The development of the expert system was based on the available analytical data of waste and carbonaceous layers and the coded descriptions of corresponding cores. The expert system was used for the estimation of quality characteristics of waste and carbonaceous layers from selected core of Southern Field mine of Ptolemais area. The quality characteristics of the estimated recoverable lignite shows a more intense fluctuation compared with this obtained by using indicative values for waste and carbonaceous layers.